Enhancing MSME Marketing Performance through AI, Creativity, and Response Speed: Lessons for Educational Management and Entrepreneurial Development - Resti Rosanabila; suhardi; Rita deseria (Al-Qalam Institue, 2026)
This study aims to examine the influence of Artificial Intelligence (AI) utilisation, marketing creativity, and response speed on the marketing performance of Micro, Small, and Medium Enterprises (MSMEs) in Bangka Belitung Province, with customer experience positioned as a mediating variable. Employing a quantitative research design, data were collected through structured questionnaires distributed to MSMEs actively engaged in digital marketing practices. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the proposed relationships. The findings indicate that marketing creativity and response speed have a significant positive effect on customer experience, whereas AI utilisation does not show a significant effect on customer experience. Furthermore, customer experience significantly influences marketing performance and serves as a mediating variable in the relationship between marketing creativity, response speed, and marketing performance. Specifically, marketing creativity and response speed contribute both directly and indirectly to improved marketing performance through enhanced customer experience. These results provide important theoretical contributions to digital marketing and customer experience literature, while offering practical implications for MSME managers and educational institutions in designing technology-oriented marketing strategies and entrepreneurship learning that prioritise creativity, responsiveness, and customer-centred approaches.